Mitochondrial DNA polymorphism and heteroplasmy in populations of aedes aegypti in Brazil - Karina Santos Paduan, D. O.S. [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP] (My University, 2008)
The tropical mosquito Aedes aegypti (Diptera: Culicidae) is the most important domestic vector of urban yellow fever and dengue viruses. Ae. aegypti originated from Africa and was probably introduced into Brazil during the colonial period through embarkations, and dengue epidemics soon followed. Genetic analysis of 12 Ae. aegypti populations from five states in Brazil was conducted based on two mitochondrial DNA fragments: cytochrome oxidase I and NADH dehydrogenase subunit 4. Analyses comparing individual haplotypes indicated the existence of two welldefined clades, probably representing two mitochondrial lineages. Analysis of molecular variance showed significant variability in genetic structure among collections within groups. Mantel regression analysis showed a correlation between genetic and geographic distances, mainly because of northern and northeastern populations, in comparison with those in the southeast. The population from Santos, the largest port in Brazil, showed the greatest diversity, with 10 unique haplotypes, an indication of recent introductions that have not yet spread to other Brazilian cities. Different mitochondrial DNA sequences were found in three specimens, indicating the presence of heteroplasmy. © 2008 Entomological Society of America.
Keywords: Aedes aegypti; Genetic variability; Heteroplasmy; Mitochondrial dna; Population genetics